Tradução e validação da escala de resiliência para crianças e adolescentes de Sandra Prince-Embury - Barbosa, Renata Jordani (2009)
Introduction: Resilience is a human potential, present in individuals in all cultures and in all times, it is part of an evolutionary process and can be promoted since the birth. Studies about resilience aim the comprehension of how children, teen-agers and adults are capable of surviving and overcome obstacles, despite living in poverty, domestic violence and other risky situations. In modern society changes are increasingly fast and deep, requiring constant efforts of adaptation and, therefore, making resilience a challenge of this new age. The current paper is relevant to psychology professional because intends to translate and validate a scale of resilience for children and teenagers, given that there are still no instrument validated specifically for these populations. Objective: Translate, adapt and validate to the Portuguese language and the Brazilian population the original version of the Resiliency Scales for Children & Adolescents (RSCA), by Sandra Prince-Embury (2007). Method: The assumptions of Hambleton e Patsula (1999) were utilized for the translation and trans-cultural adaptation of the scale. Data gathering for the research was made in three schools (two public and one private) located in different communities in the city of Sao Paulo The sample size was 1226 children and teen-agers from 9 to 18 year old, 51% of those female. Outcomes: In order to verify the factors that compound the sub-scales CO, CR e RA, the author used factorial analysis for principal components and Varimax rotation. Factorial charges equal or greater than 0.3 were assumed and the adequacy of factorial analysis was verified according to KMO coefficient and Bartlett sphere test. Alpha Cronbach scores found in the Brazilian version (CO = 0.83, CR = 0.90 e RA = 0.87) were considered satisfactory compared to the results related by Prince- Embury (2007), indicating good internal consistent of the tool. The alpha coefficients were considered relevantly lower that the original ones in only three factors (adaptability, comfort and tolerance). Several concepts defined in this paper are theoretically related to themselves, reason why the formation of some factors shows that the items are ambiguous. This ambiguity was reflected in the factorial analysis. The factors that showed this relation were: optimism and self-efficacy (CO scale); trust and support (CR scale)